2006
DOI: 10.1001/jama.295.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury and Long-term Mortality Following Moderate to Severe Carbon Monoxide Poisoning

Abstract: Myocardial injury occurs frequently in patients hospitalized for moderate to severe CO poisoning and is a significant predictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
186
2
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(204 citation statements)
references
References 38 publications
5
186
2
11
Order By: Relevance
“…In patients felt to be at low risk for coronary artery disease, 37% suffered myocardial injury and 38% were dead within roughly 7.5 years. This mortality rate was three times higher than expected after controlling for age and gender [11].…”
Section: Biochemistry Physiopathology and Pathologycontrasting
confidence: 55%
“…In patients felt to be at low risk for coronary artery disease, 37% suffered myocardial injury and 38% were dead within roughly 7.5 years. This mortality rate was three times higher than expected after controlling for age and gender [11].…”
Section: Biochemistry Physiopathology and Pathologycontrasting
confidence: 55%
“…It was represented that myocardial injury, assessed by CK-MB or CTI elevation, occurred in 44% of patients with biomarkers drawn (Satran et al, 2005). Electrocardiograph (ECG) findings and/or elevation of serum CTI and/or CK-MB levels were underscored as integral criteria for the assessments of cardiac injuries caused by COP (Henry et al, 2006;Satran et al, 2005). Our clinical experiences were also relevant to these observations.…”
mentioning
confidence: 91%
“…Myocardial injury was found to be a significant predictor of mortality related to COP (Henry et al, 2006;Satran et al, 2005). It was represented that myocardial injury, assessed by CK-MB or CTI elevation, occurred in 44% of patients with biomarkers drawn (Satran et al, 2005).…”
mentioning
confidence: 99%
“…1 In addition to its well-described neurological toxicity, clinically, CO poisoning may lead to myocardial ischemia, manifested by chest pain, electrocardiogram changes (ST-segment depression and T-wave depression), and myocardial infarction, and is associated with long-term morbidity and mortality. 2,3 Previous animal studies have suggested that CO may produce direct toxicity to the myocardium rather than indirect hypoxic damage. 4 Experimentally, CO has been shown to decrease regional myocardial segment work and increase coronary flow with increasing concentrations; however, the site and mechanism of CO myocardial toxicity has not been elucidated.…”
mentioning
confidence: 99%
“…11 Recent clinical studies have demonstrated that morbidity and mortality from cardiac causes are related to an episode of moderate to severe CO poisoning. 3 The objective of this laboratory study is to show that CO causes depression of cardiac performance using the left ventricular generated pressure (LVGP) as an indicator of function in the ex vivo isolated rat heart model and that this toxic effect on the heart is distinct from hypoxemic hypoxia. We define ''hypoxemia'' as a lower partial pressure of oxygen in our perfusion solution and ''hypoxia'' as diminished oxygen delivery to the heart, evident by increased lactic acid in the effluent.…”
mentioning
confidence: 99%